Pemahaman Kasih Karunia Berdasarkan Roma 3:23-24 Dalam Integritas Akademik Mahasiswa - Kana Mangngi, Priska Natalia; Sianturi, Juliana (STIPAK Malang, 2023)
Romans 3:23-24 says that “all have sinned and fall short of the glory of God, and are justified freely by grace through the redemption that is in Christ Jesus.” This verse explains that all people are sinners by nature, and had indeed sinned, and had fallen short of the glory of God. Then, academic integrity is behavior that is honest, fair, and fulfills academic morals carried out by someone. The purpose of this study was to determine the understanding of grace of STIPAK Malang students in semester VIII of the academic year 2021/2022 based on Romans 3:23-24, academic integrity of STIPAK Malang students in semester VIII of the academic year 2021/2022, and understanding of grace based on Romans 3:23- 24 in the academic integrity of STIPAK Malang students in semester VIII of the 2021/2022 academic year. The research method used in this research is qualitative with a phenomenological approach. The results of the research are that the understanding of STIPAK Malang students for the 2021/2022 academic year about grace based on Romans 3:23-24 has not been fully implemented in academic integrity, but is still being tried to be applied. The advice given by researchers to STIPAK Malang students for the 2021/2022 academic year is to have academic integrity because they already understand grace and are also prospective PAK teachers.